The effect of cash transfers on fertility: evidence for Argentina - Garganta, Santiago (2014)
In 2009 Argentina implemented a large poverty-alleviation program (AUH) that provides monthly cash transfers per child to households without workers in the formal sector. In this paper we estimate the potential unintended effect of that program on fertility decisions using a diff-in-diff strategy. The results suggest a significant positive impact on fertility in those households with already at least one child (around 2 percentage points), but no significant effect on those households without children. We are unable to identify whether the positive effect in the former group reflects changes in the time pattern of fertility or in the equilibrium number of children.